2015
DOI: 10.11646/zootaxa.3920.2.8
|View full text |Cite
|
Sign up to set email alerts
|

New records of sea lice (Copepoda: Caligidae) from marine fishes in Jaramijó, an area with potential for sea-cage aquaculture in Ecuador

Abstract: Farming of finfish in sea cages is gaining popularity worldwide. These systems are a suitable environment for the emergence, establishment and transmission of parasites or pathogens, such as sea lice (Copepoda: Caligidae), known to cause serious diseases and economic losses in finfish aquaculture worldwide. In coastal waters of Jaramijó, Ecuador, there are plans to culture spotted rose snapper (Lutjanus guttatus) and longfin yellowtail (Seriola rivoliana); however, the information about the occurrence of sea l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 38 publications
2
6
1
Order By: Relevance
“…The morphology of our specimens (♂ and ♀) fits with the description of Ho and Lin (2004). Additionally, based on the examination of the present material and also that from previous surveys in the Eastern Pacific (Morales-Serna et al 2014, 2015), we suggest that the shape of the first segment of the antenna and sternal furca may be useful in identifying C.confusus . Clearly, C.confusus has high affinity for carangid fish; nonetheless, this parasite can also be found on fish from different families.…”
Section: Resultssupporting
confidence: 82%
See 3 more Smart Citations
“…The morphology of our specimens (♂ and ♀) fits with the description of Ho and Lin (2004). Additionally, based on the examination of the present material and also that from previous surveys in the Eastern Pacific (Morales-Serna et al 2014, 2015), we suggest that the shape of the first segment of the antenna and sternal furca may be useful in identifying C.confusus . Clearly, C.confusus has high affinity for carangid fish; nonetheless, this parasite can also be found on fish from different families.…”
Section: Resultssupporting
confidence: 82%
“…Several copepods species can parasitize multiple fish species (Dojiri and Ho 2013). This is the case of C.mutabilis found on Lutjanusmonostigma and L.fulvus in the present study however, this species has been reported in at least 13 families of marine fishes from the Atlantic and Pacific oceans (Morales-Serna et al 2015).…”
Section: Discussioncontrasting
confidence: 39%
See 2 more Smart Citations
“…According to Walter and Boxshall (2021), the family Caligidae comprises 63 genera, which include ~911 valid species, 440 of which belong to the genus Caligus . The predominance of Caligus found in our study is consistent with what was reported by Morales‐Serna et al (2015), who analyzed 23 host species from the coast of Ecuador and also found several species of Caligus (22 spp. ), thus confirming the high abundance of this family as a parasite of marine fish in Ecuadorian waters.…”
Section: Discussionsupporting
confidence: 93%